Southeast Asia and the Middle East: Islam, Movement, and the Longue Durée by Eric Tagliacozzo, ed. (Stanford: Stanford University Press, 2009. 360 pages.) (American Journal of Islam and Society, 2010)
As part of a growing interest in global and transnational patterns connectingdifferent parts of the Muslim world, scholarship on Islam in Southeast Asia,which has long suffered from what Robert Hefner once called a “double marginalisation” in the work of both Islamicists and Asianists, has made considerable progress in mapping the networks connecting Dar al-Islam’seastern geographical peripheries with its perceived Middle Eastern “heartland.”And while Cornell historian Eric Tagliacozzo notes that several studiesdeal with the history of the commercial, educational, and religiousexchanges between the Hijaz and insular Southeast Asia, making good forthe “paucity of historiography of this particular transregional dialogue,” hesees his edited volume as filling the lacuna on “what the parameters of thislong-distance dialogue between civilizations have meant over the centuries”(p. 1). Using Fernand Braudel’s notion of longue durée as a rubric, he hasgrouped the collected essays under the respective headings of “The EarlyDimensions of Contacts,” “The Colonial Age,” “The First Half of the 20thCentury,” and “Into Modernity.” ...